Antiplatelet Efficacy in Outpatient Post-Ischaemic Stroke Patients at Dr. Saiful Anwar Malang City General Hospital - Alfazahrah, Azki; Triastuti, Efta; Achmad, Anisyah (Brawijaya University, 2026)
Introduction: According to WSO (World Stroke Organization) in 2022, stroke is the second leading cause of disability and death worldwide. One of the treatments for ischemic stroke is Antiplatelet. Antiplatelet therapy is said to have a significant effect in the management of ischemic stroke and secondary stroke prevention. Various types of antiplatelets are used but the effectiveness of each drug in improving clinical conditions such as hemiparesis still requires further research. In this study, the Hemiparesis Improvement Score was used in clinical practice at Dr. Saiful Anwar General Hospital Malang City to make it easier to see clinical conditions directly. Objectives: This study aims to analyze the effectiveness of antiplatelet based on clinical parameters of hemiparesis in outpatients after ischemic stroke at Dr. Saiful Anwar General Hospital Malang City. Methods: This study used a retrospective analytic observational method with secondary data in the form of medical records of ischemic stroke outpatients undergoing antiplatelet therapy. Data collection was carried out by purposive sampling with a total sample of 155 patients with an intervention time setting of at least 3 months. Data analysis was performed using Odds Ratio Multinominal Regression and Chi-Square Test to evaluate the treatment effect on clinical parameters of hemiparesis, hemiparesis improvement time and comorbid analysis as confounding factors. Bonferroni Post Hoc Test was performed for further analysis. Results: The results showed that the combination of clopidogrel and aspirin (P- value adjusted (Bonferroni post hoc) = 0.0228) provided significant improvement in hemiparesis compared to aspirin monotherapy (OR = 0.320; P-value = 0.035); P-value adjusted (Bonferroni post hoc) = 1.6857), clopidogrel (OR = 0.295; P-value = 0.029; P- value adjusted (Bonferroni post hoc) = 1.3239), or cilostazole (OR = 0.250; P-value = 0.013; P-value adjusted (Bonferroni post hoc) = 0.5506). Kruskall Wallis test in month 2 cilostazole improved hemiparesis (Mean rank = 93.41; Sig.= 0.043; Sig.adj (Dunn Test) = 0.045) and in month 3 the combination of aspirin clopidogrel improved hemiparesis (Mean rank = 84.21; Sig.= 0.030; Sig.adj (Dunn Test) = 0.026). From this study it can be concluded that the combination of clopidogrel and aspirin is effective in improving the clinical condition of post-ischemic stroke patients based on hemiparesis parameters. Conclusion: Based on this study, it is suggested to be able to consider additional factors such as the level of patient compliance and the effect of physical rehabilitation in accelerating the improvement of hemiparesis.